Adverse childhood experiences are associated with increased risk of hysterectomy and bilateral oophorectomy: A national retrospective cohort study of women in England. (8th February 2022) - Demakakos, Panayotes; Steptoe, Andrew; Mishra, Gita D.
Abstract: Objective: To examine the associations between adverse childhood experiences (ACE) and the risk of hysterectomy and bilateral oophorectomy in a national sample of women in England. Design: Retrospective cohort study. Setting: A stratified random sample of households across England. Population: 2648 women aged ≥55 years in 2007 from the English Longitudinal Study of Ageing (ELSA) were included in the bilateral oophorectomy analyses and 2622 in the hysterectomy analyses. Methods: Logistic and multinomial logistic regression analyses of the associations between categories of the ACE summary score (0, 1, 2, ≥3 ACE), eight individual ACE, and hysterectomy and bilateral oophorectomy. Results: 615 women had undergone hysterectomy and 259 women bilateral oophorectomy. We found graded associations between the summary ACE score and risk of hysterectomy and bilateral oophorectomy. In the fully adjusted model, compared with women with no ACE, those with ≥3 ACE had double the odds of hysterectomy (odds ratio [OR] 2.01, 95% confidence interval [CI] 1.30–3.11) and more than double the odds of bilateral oophorectomy (OR 2.61, 95% CI 1.54–4.42). The exclusion of women with cancer history made the associations stronger, especially in women who underwent hysterectomy at age <40 years or bilateral oophorectomy at age ≤44 years. Several individual ACE were positively associated with both outcomes. Conclusions: ACE are associated with increased risk of hysterectomy and bilateral oophorectomy. Individual‐level covariates did not explain these associations. Our findings highlight the importance of a life course approach to understanding surgical menopause and add to our knowledge of the societal and public health impact of ACE. Tweetable abstract: Adverse childhood experiences are associated with increased risk of hysterectomy and bilateral oophorectomy in a national sample of women in England. Tweetable abstract: Adverse childhood experiences are associated with increased risk of hysterectomy and bilateral oophorectomy in a national sample of women in England. Linked article: This article is commented on by Walter A. Rocca, pp. 1491–1492 in this issue. To view this minicommentary visit https://doi.org/10.1111/1471-0528.17105 .